Sandwich EVAR occludes Celiac and Superior Mesenteric Artery for Infected Suprarenal Abdominal Aortic Aneurysm Treatment - Supatcha Prasertcharoensuk; Narongchai Wongkonkitsin; Parichat Tunmit; Su-a-pa Theeragul; Anucha Ahooja (Case Reports in Vascular Medicine)
Introduction. Infected aortoiliac aneurysms are rare, representing only 1% to 2% of all aortic aneurysms; we present a case of infected suprarenal aortic aneurysm with a nearly occluded celiac artery and superior mesenteric artery treated using an endovascular technique to preserve collateral in the retroperitoneal space from the inferior mesenteric artery for supplying visceral organs.